Some results and examples on vertex equitable labeling - Aboshady, Mohamed; Seoud, Mohamed; Elbarkouky, Reda; Roshdy, Eliwa (Utilitas Mathematica, 2019)
In this paper we present a survey for all graphs with order at most 6 whether they are vertex equitable or not and we get an upper bound for the number of edges of any graph with p vertices to be a vertex equitable graph. Also, we establish vertex equitable labeling for the m-chain of the complete bipartite graph K2,nand for the graphPn×Pm. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.